DEVELOPMENT OF AUGMENTED REALITY BASED SNAKES AND LADDERS GAME TO ENHANCE SOCIAL STUDIES LEARNING MOTIVATION AND ENVIRONMENTAL AWARENESS - Ardania; Prastiyono, Hendri; Segara, Nuansa Bayu; Hasanah, Nurul; Dizon, Carmela S. (Universitas Muhammadiyah Surakarta, 2025)
This study aims to develop a snake and ladder game media based on Augmented Reality that is feasible and effective in increasing the motivation to learn social studies and environmental awareness. This development research uses the Borg and Gall model modified into 8 stages, namely (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision (6) product trial (7) product revision (8) usage trial. The research design uses a quasi-experimental design with nonequivalent controlgroup design. This study involved media experts, material experts, social studies teachers, and eighth-grade students of SMP Labschool UNESA 2. Data were collected through interviews, observations, questionnaires, and tests. The results of the study showed that the snake and ladder game media based on augmented reality was declared